METHODOLOGICAL DIRECTIONS FOR THE REGULATION OF INVESTMENTS IN MACROECONOMIC PROCESSES - Saida Ahmadjanovna Abdurahimova (Scholar Express Journals, 2023)
The article describes the directions for the regulation of investment processes, the scientific-methodical approach of macroeconomic regulation of investment processes and the methodological aspects of macroeconomic regulation of investment processes in ensuring sustainable economic growth.
Keywords: investment; investment process; macroeconomic regulation; unemployment